2018
DOI: 10.1037/pas0000508
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a Spanish language assessment of children’s social-emotional learning skills.

Abstract: Few Spanish language tools are available for assessing important social-emotional learning (SEL) skills. The present study presents evidence of the psychometric properties of a Spanish-language version of SELweb (SELweb-S), a web-based system for assessing children's ability to recognize others' emotions and perspectives, solve social problems, and engage in self-control. With a sample of 524 students in Grades K to 3, we examined the reliability and validity of SELweb-S. This study provided evidence that (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In four separate studies examining SELweb and other assessments, McKown, Allen, Russo-Ponsaran, and Johnson (2013) and McKown and colleagues (2016) found that (a) composite social-emotional assessment scores exhibited latent factor internal consistency reliabilities (Nunnally & Bernstein, 1994) averaging greater than .80; (b) social-emotional assessment observed scores fit a four-factor structure reflecting emotion recognition, social perspective-taking, social problem-solving, and self-control; (c) social-emotional comprehension factor scores demonstrated convergent and discriminant validity; and (d) controlling for IQ and demographic characteristics, performance on SELweb was positively associated with peer acceptance, teacher report of social skills, and multiple indicators of academic achievement, and negatively associated with teacher report of problem behaviors. Evidence of the reliability and validity of a Spanish language version SELweb is consistent with these findings (Russo, McKown, Russo-Ponsaran, & Allen, 2018).…”
Section: Selweb To Assess Social-emotional Comprehensionmentioning
confidence: 52%
“…In four separate studies examining SELweb and other assessments, McKown, Allen, Russo-Ponsaran, and Johnson (2013) and McKown and colleagues (2016) found that (a) composite social-emotional assessment scores exhibited latent factor internal consistency reliabilities (Nunnally & Bernstein, 1994) averaging greater than .80; (b) social-emotional assessment observed scores fit a four-factor structure reflecting emotion recognition, social perspective-taking, social problem-solving, and self-control; (c) social-emotional comprehension factor scores demonstrated convergent and discriminant validity; and (d) controlling for IQ and demographic characteristics, performance on SELweb was positively associated with peer acceptance, teacher report of social skills, and multiple indicators of academic achievement, and negatively associated with teacher report of problem behaviors. Evidence of the reliability and validity of a Spanish language version SELweb is consistent with these findings (Russo, McKown, Russo-Ponsaran, & Allen, 2018).…”
Section: Selweb To Assess Social-emotional Comprehensionmentioning
confidence: 52%
“…There are few assessments that are available to measure SIP in English language learners. A trans‐adapted, Spanish‐language version of VESIP was also developed during the course of this study, making it one of less than a handful of Spanish‐language assessments for youth (e.g., Bar‐On & Parker, 2000; Gresham & Elliott, 2008; Russo et al., 2018). To date, only a small number of youth have completed that version, but a related large‐scale validation effort for use by English‐language learners is planned.…”
Section: Discussionmentioning
confidence: 99%
“…To address the gap, we created SELweb Early Elementary (“SELweb EE”), a web-based system for directly assessing social and emotional competence in kindergarten through third grades (McKown, Russo-Ponsaran, Johnson, et al, 2016; Russo et al, 2018). SELweb EE presents items and response options pictorially with audio narration and few written words.…”
mentioning
confidence: 99%